Teach Yourself World Cultures: China - Kenneth Wilkinson
Why was the Long March so long? How does Chinese medicine work? Is China the world's last communist superpower? What is the mysterious force called 'qi'? This book answers these questions, and many more, in a concise and lively overview of China: the country, its languages, its people, their way of life and culture and what makes them tick. If you are studying for examinations which require a knowledge of the background of China and its civilisation, or if you are learning the language in, for example, an evening class and want to know more about the country, this is the book for you. If your job involves travel and business relations, it will provide valuable and practical information about the ways and customs of the people you are working with. Or if you simply have an interest in China for whatever reason, it will broaden your knowledge about the country and its inhabitants. The book is divided into three sections. Chapters One and Two deal with the forces - historical, geographical, geological, demographical and linguistic - that have brought about the formation of the country we know as China and the language we know as Chinese. Chapters Three to Seven deal with the wealth of creative aspects of Chinese culture from the beginnings to the present day. These chapters take a look at the main areas or works of philosophy and religion, festivals and folklore, literature, entertainment, art and architecture, music, food, crafts and other facets of Chinese ingenuity, together with the people who have created and are still creating them. Chapters Eight to Thirteen deal with aspects of contemporary Chinese society and the practicalities of living in present-day China: the recent political history and present political structure of the country, education, work and leisure, health and Chinese medicine and the Chinese attitude to the family and sex. The final chapter takes a glance at the future. Each chapter ends with a section entitled 'Taking it Further', where you will find useful addresses, websites and things to see and do. Each chapter also contains a list of useful words and phrases which will help you to talk or write about the subject in question. The new edition takes into account any developments in Chinese culture and society which have occurred since first publication.